An outbreak of group B meningococcal disease: tracing the causative strain of Neisseria meningitidis by DNA fingerprinting. - Kristiansen, B E (1986)
Following an outbreak of meningococcal disease in three schoolchildren in a small community in northern Norway, DNA fingerprinting, serotyping with monoclonal antibodies, serogrouping, and sulfonamide sensitivity testing were applied for characterization and tracing of the causative agent. The three case isolates were genomically indistinguishable, sulfonamide-resistant, serogroup B, serotype 15 meningococci. Throat specimens were collected from 552 healthy contacts, including all children below age 17 and their parents. Among the 36 carrier isolates (carrier rate, 6.5%) 13 showed DNA fingerprints identical, or almost identical, to the index pattern. All of these 13 isolates were sulfonamide resistant, 12 were of serotype 15, and 8 were of polysaccharide serogroup B (5 were nongroupable). These closely related isolates were almost exclusively recovered from schoolchildren of 2 of 15 small villages, one of which included the homes of two of the patients. The remaining 23 carrier isolates were nonresistant, non-type 15 meningococci of widely differing DNA restriction patterns. Our results confirm that DNA fingerprinting has potential as an efficient tool in practical meningococcal epidemiology.